2022
DOI: 10.1111/jse.12826
|View full text |Cite
|
Sign up to set email alerts
|

Northern gene flow into southeastern East Asians inferred from genome‐wide array genotyping

Abstract: The population history of Southeast (SE) China remains poorly understood due to the sparse sampling of present‐day populations and limited modeling with ancient genomic data. We report genome‐wide genotyping data from 207 present‐day Han Chinese and Hmong‐Mien (HM)‐speaking She people from Fujian and Taiwan Island, SE China. We coanalyzed 66 Early Neolithic to Iron Age ancient Fujian and Taiwan Island individuals obtained from previously published works to explore the genetic continuity and admixture based on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Han Chinese is the largest ethnic group in the world and has a significant influence on the formation of the gene pool of Chinese populations [37, 38, 55-57]. To further explore phylogenetic topology among Han Chinese and illuminate the genetic relationship between Han Chinese and aforesaid minorities, we collected and genotyped 711 individuals via Affymetrix array, which included 690 Han Chinese from 25 geographically different populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Han Chinese is the largest ethnic group in the world and has a significant influence on the formation of the gene pool of Chinese populations [37, 38, 55-57]. To further explore phylogenetic topology among Han Chinese and illuminate the genetic relationship between Han Chinese and aforesaid minorities, we collected and genotyped 711 individuals via Affymetrix array, which included 690 Han Chinese from 25 geographically different populations.…”
Section: Resultsmentioning
confidence: 99%
“…However, Chinese populations possessed complex cultural, geographical, ethnic and genetic diversity patterns, these dedicated Y-SNP genotyping tools could not cover the dominant paternal lineages of Chinese populations and meet the requirement of high-resolution paternal lineage classification. Whole-genome sequencing-based genetic studies have illuminated Chinese population structures strongly correlated with the geographical regions or language families [37, 38]. Ancient DNA of East Eurasians further identified the westward steppe pastoralist ancestry, north-to-south di-directional population movements along the Yangtze River and Yellow River basins, peopling of the Tibetan Plateau and extensive interaction with ancient Siberians [39-43].…”
Section: Introductionmentioning
confidence: 99%
“…Ancient population substructures in East Asia were also observed in modern East Asians. Our previous genetic studies identified genetic substructures in the Amur River, Tibetan Plateau, and inland and coastal South China associated with geographic locations and linguistic affiliations [13,[19][20][21]. However, these efforts have been made primary foundational work to dissect the mystery of Chinese populations' evolutionary and adaptive history.…”
Section: Introductionmentioning
confidence: 99%
“…Altaic-speaking populations in North China showed predominant ancestry related to ancient Mongolian ancestry and western Eurasian ancestry [14,15]. Other populations from Sino-Tibetan language families in central and southern East Asia harboured more primary ancestry related to ancient Yellow River Basin and Yangtze River Basin ancestry [9,10,16]. These population stratifications provided a new opportunity for the development and validation of new forensic kits focused on the fine-scale genetic background of East Asians with different genetic markers and higher resolution.…”
Section: Introductionmentioning
confidence: 99%